2014
DOI: 10.1371/journal.pone.0099946
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-Secreted Factors Promote Proliferation and Osteogenic Differentiation of Bone Marrow Stromal Cells via VEGF/Heme-Oxygenase-1 Pathway

Abstract: The hypoxia-inducible factors (HIFα) are the critical factors that couple angiogenesis and osteogenesis by activating transcription of VEGF in osteoblasts. Mice lacking von Hippel–Lindau gene (Vhl), thus overexpressing HIFα in osteoblasts develop extremely dense and highly vascularized long bones. Here we provide evidence that osteoblasts lacking Vhl overexpress and secrete high levels of VEGF, which subsequently promotes the proliferation and osteogenic differentiation of bone marrow stromal cells (BMSC) by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 38 publications
1
26
0
Order By: Relevance
“…To investigate whether the observed defect in mineralization in male OBVEGFKO mice was driven by direct effects of VEGF on LOB function, we deleted VEGF with adenovirus-Cre-GFP as previously described. (26) Consistent with our previous work, (29) LOBs did not express detectable levels of VEGFR2 protein or mRNA (Supplemental Fig. S8A, C).…”
Section: In Vitro Vegf Deletion Induces Distinct Matrix and Mineralizsupporting
confidence: 91%
See 1 more Smart Citation
“…To investigate whether the observed defect in mineralization in male OBVEGFKO mice was driven by direct effects of VEGF on LOB function, we deleted VEGF with adenovirus-Cre-GFP as previously described. (26) Consistent with our previous work, (29) LOBs did not express detectable levels of VEGFR2 protein or mRNA (Supplemental Fig. S8A, C).…”
Section: In Vitro Vegf Deletion Induces Distinct Matrix and Mineralizsupporting
confidence: 91%
“…In vitro deletion of osteoblast-derived VEGF Once 80% confluent, LOBs were treated with adenovirus-Cre-GFP (Vector Laboratories, Burlingame, CA, USA) in growth media containing 10% FBS for deletion of VEGF or adenovirus-GFP as a control at a multiplicity of infection of 100 for 6 days. (26) For cell viability/proliferation only, LOBs were treated with Adenovirus-Cre-GFP (denoted OBVEGFKO) and Adenovirus-GFP (denoted WT) for 24 hours. For collection of conditioned media (CM), cells were stepped down in lowserum media (1%) for 24 hours.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…It was noted that there was no new bone formation in this study. Similarly, Zhang et al 42 found that the single VEGF from the silk gel or silk scaffold only promoted angiogenesis and more tissue infiltration into the gel or scaffold, in which no bone regeneration was observed, while combining VEGF and BMP-2 released from the silk gel or silk scaffold could promote angiogenesis and new bone formation. 48,49 Besides, graft motion in the bone tunnel could be inevitable in ACL reconstruction model, which impeded bone regeneration.…”
mentioning
confidence: 95%
“…41 The proliferation level of BMSCs in the UHMWPE-SF/VEGF group was significantly higher than that of the UHMWPE-SF group after 14-day cultivation, because the sustained VEGF release was conductive to BMSC proliferation and adhesion. Zhang et al 42 demonstrated that VEGF stimulated the proliferation and osteogenic differentiation of BMSC by promoting the expression of heme oxygenase-1. Besides, VEGF regulated BMSC fate by increasing osteoblast differentiation and reducing adipocyte differentiation.…”
mentioning
confidence: 99%
“…On the contrary, HO-1 expression induced by Hemin accelerated the cell cycle progression to G2/M phase (Fig. 3), probably by promoting cell proliferation and differentiation (15,16). ylation (17,18).…”
Section: Aza Treatment Increases Ho-1 Expression In Skm-1 Cellsmentioning
confidence: 96%